Evaluating the Status of and African Wild Dogs Lycaon pictus and Cheetahs Acinonyx jubatus through Tourist-based Photographic Surveys in the Kruger National Park - Marnewick, Kelly (Public Library of Science, 2014)
The Kruger National Park is a stronghold for African wild dog Lycaon pictus and cheetah Acinonyx jubatus conservation in South Africa. Tourist photographic surveys have been used to evaluate the minimum number of wild dogs and cheetahs alive over the last two decades. Photographic-based capture-recapture techniques for open populations were used on data collected during a survey done in 2008/9. Models were run for the park as a whole and per region (northern, central, southern). A total of 412 (329–495; SE 41.95) cheetahs and 151 (144–157; SE 3.21) wild dogs occur in the Kruger National Park. Cheetah capture probabilities were affected by time (number of entries) and sex, whereas wild dog capture probabilities were affected by the region of the park. When plotting the number of new individuals identified against the number of entries received, the addition of new wild dogs to the survey reached an asymptote at 210 entries, but cheetahs did not reach an asymptote. The cheetah population of Kruger appears to be acceptable, while the wild dog population size and density are of concern. The effectiveness of tourist-based surveys for estimating population sizes through capture-recapture analyses is shown.